Pharmacological mechanisms of traditional Chinese medicine metabolites in regulating Treg cells: an integrative pathway review - Wang, Chao; Liao, Ming-Jie; Wu, Yao; Lin, Heng; Ye, Zhen-Zhong; Ma, Wen-Zhe; Yuan, Qing (Frontiers in Pharmacology, 2025)
BackgroundRegulatory T cells (Tregs), characterized by the transcription factor Foxp3, play a pivotal role in maintaining immune homeostasis, preventing autoimmunity, and contributing to tumor immune evasion. Traditional Chinese Medicine (TCM), with its long history of clinical application, exerts unique regulatory effects on immune responses. However, a comprehensive mechanistic synthesis of TCM-mediated Treg regulation remains lacking.MethodsWe reviewed studies from PubMed up to August 2025, focusing on molecular, cellular, and microbiota-related mechanisms by which TCM modulates Tregs. Identified evidence was synthesized into four major mechanisms and further integrated into three regulatory axes.ResultsTCM regulates Tregs through four mechanisms: (1) Foxp3 expression regulation mechanisms; (2) IL-2 receptor pathway mechanisms; (3) Regulation of other Treg surface molecules; and (4) Gut microbiota modulation mechanisms. These four mechanisms converge into three regulatory axes: the core execution axis (direct Foxp3 control), the upstream regulatory axis (cytokine and receptor crosstalk), and the cross-boundary integration axis (gut microbiota–immune interactions).ConclusionThis review proposes an integrated framework that refines four regulatory mechanisms into three axes, highlighting the multi-layered and interconnected pathways through which TCM shapes Treg biology. This systems-level perspective provides a theoretical basis for developing TCM-derived strategies in immune-mediated diseases and cancer immunotherapy.